Single-pot formation of THFAL via catalytic hydrogenation of FFR over Pd/MFI catalyst - Biradar, Narayan S.; Hengne, Amol M.; Birajdar, Shobha N.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (ACS Sustainable Chemistry & Engineering, 2014)
Furfural (FFR) was selectively hydrogenated in a single pot to tetrahydrofurfuryl alcohol (THFAL) over a Si MFI molecular sieve supported Pd catalyst. Studies on catalyst screening revealed that both the metal function and the support were critical for directing the selectivity to the ringhydrogenated product, THFAL. The structural feature of MFI as shown by XRD was completely retained in the used sample of the 3% Pd/MFI catalyst confirming its stability under reaction conditions. XRD, along with SEM characterization of the used samples, established retention of morphology of the structured silicate, suggesting a strong interaction between hexagonal porous silicate and Pd particles. The complete conversion of FFR with an enhanced selectivity of 95% to THFAL could be achieved by recycling the crude of the first hydrogenation experiment over the same 3% Pd/MFI catalyst.
Keywords: Biomass conversion; Hydrogenation; Pd/MFI; Recyclability; THFAL

Tailoring the product dstribution with batch and continuous process options in catalytic hydrogenation of furfural - Biradar, Narayan S.; Hengne, Amol A.; Birajdar, Shobha N.; Swami, Rameshwar; Rode, Chandrashekhar V. (Organic Process Research & Development, 2014)
Various noble metal catalysts were screened in a batch operation for a furfural (FFR) single-step decarbonylation and hydrogenation reaction to obtain THF in high selectivity. Among these, the 3% Pd/C showed complete FFR conversion with a total of 80% selectivity to ring hydrogenated products including tetrahydrofuran (THF). The order of activity exhibited by other noble metals was Pt/C > Re/C > Ru/C. Although Pt/C exhibited the highest activity, its decarbonylation and ring hydrogenation ability were the least (24%) with a major product selectivity of 66% to furfuryl alcohol (FAL). Similarly, the Cu catalyst gave almost complete selectivity to FAL. In a continuous operation (23 g catalyst bed), the 3% Pd/C catalyst showed higher selectivity of >40% compared to THF alone with complete FFR conversion and on-stream activity of similar to 100 h. The reaction pathway elucidated from some control experiments revealed that the decarbonylation of FFR to furan over the Pd/C catalyst is a prerequisite for THF formation.